The Anthropology of Historical Photography in a Protected Area: Life and Death in Waterton Lakes National Park, Alberta - Smith, Trudi Lynn (Anthropologica, 2014)
This article offers an ethnographic and anthropol ogical investigation of historical photography carried out in Waterton Lakes National Park, Alberta. I recount my attempts to precisely retake a photograph from its historical location. Once there, I scrutinize photography's presences to better understand how a photograph emerges as an event. Photogra phy can be used to understand human-wind encounters, the force of effort, the conventions that shape place, the impact of available water and how these come to bear on visibility and invisibility, life and death, in the present.